SlSPA3 regulates the nuclear abundance of SlUVR8 in tomato - Zhang, Qianwen (2024)
Tomato (Solanum lycopersicum L.) is an important model plant species in photomorphogenesis research. Ultraviolet B (UV-B) induces the dissociation of homodimers of the photoreceptor UV RESISTANCE LOCUS8 (UVR8) into monomers, which translocate into the nucleus. Nuclear accumulation of UVR8 is a prerequisite for its signaling function. Previous studies have reported that SUPPRESSOR OF PHYTOCHROME A-105 (SPA) family members may regulate UV-B signaling in Arabidopsis (Arabidopsis thaliana); however, the underlying mechanism is unknown. Here, we show that the tomato genome encodes four SPA (SlSPA) orthologs. Genome-edited Slspa3 mutants exhibited enhanced photomorphogenic responses in white light, suggesting that SlSPA3 inhibits general photomorphogenesis. By contrast, UVR8-mediated gene expression in response to UV-B was compromised in Slspa3 mutants, suggesting that SlSPA3 promotes UV-B signaling. UV-B-induced nuclear accumulation of UVR8, which is essential for UV-B signaling, was reduced in the Slspa3 mutants. Moreover, UV-B-induced nuclear accumulation of UVR8 was also reduced in the Arabidopsis spa1 spa2 spa3 and spa1 spa2 spa4 triple mutants, indicating a conserved mechanism in these two species. Notably, spa1 spa2 spa4 exhibited normal UV-B-induced interaction between UVR8 and the plant morphogenesis repressor CONSTITUTIVE PHOTOMORPHOGENIC 1 (COP1). This suggests that the well-established mechanisms of UVR8 nuclear retention remained unaffected in spa1 spa2 spa4. Thus, our work uncovered a potentially unrecognized mechanism by which SPA proteins regulate UV-B signaling through the promotion of UVR8 nuclear abundance in land plants.